Pyrogenic and neuroinflammatory properties of zymosan and its potential as an alternative to live yeast in antipyretic drug testing - Rachael Dangarembizi; Christoph D. Rummel; Joachim Roth; Kennedy H. Erlwanger; Michael T. Madziva; Lois M. Harden (Canadian Science Publishing, 2019)
Zymosan, an immunogenic cell wall extract of Saccharomyces cerevisiae has potential for use as an experimental pyrogen. However, the short-lived sickness responses noted with intraperitoneal and intra-articular administration of zymosan limits investigations on the long-term effectiveness of antipyretic drugs. Thus, there remains a need to establish an alternative route of zymosan administration that could induce long-lived fevers and inflammation. We injected male Sprague Dawley rats (250-300 g) subcutaneously with zymosan (30 or 300 mg/kg) or saline; n = 7-8. We measured core body temperature, cage activity, food intake and body mass for 24 h after injection. Blood and brain samples were collected at 2, 8, and 18 h after injection. Zymosan (300 mg/kg) induced fever, lethargy, and anorexia, which lasted for 24 h. Zymosan-induced sickness responses were accompanied by increased blood plasma levels of interleukin (IL)-6 and tumor necrosis factor (TNF)-α; activation of inflammatory transcription factors (nuclear factor (NF) for IL-6, signal transducer and activator of transcription (STAT)-3, and NF-κB) in the hypothalamus and circumventricular organs; and increased hypothalamic mRNA expression of TNF-α, IL-1β, and IL-6 and rate-limiting enzymes for prostaglandin synthesis. Our results confirm the suitability of subcutaneous administration of zymosan for screening antipyretic and anti-inflammatory drugs in rats.